Conceptual Model of Informal Business Development Based on Intellectual Capital - Tinneke Evie Meggy Sumual; Muhammad Amir Arham; Arie Kawulur; Rocky Rimbing (AIBPM Publisher, 2021)
This paper aims to describe the conceptual model of informal business development applied to “Tibo-Tibo” fisherwomen in North Minahasa Regency. Data and information were obtained by observation and structured interviews to “Tibo-Tibo” fisherwomen, business partners and village governments. The data was analyzed qualitatively by using Miles Huberman perspective, through stages: data reduction, data presentation, conclusion drawing and verification. After going through the validity of experts, this paper produced a conceptual model of informal business development based on intellectual capital namely human capital, social capital and organizational capital. This paper recommends that through the intellectual capital approach